Influence of Sulfate-Reducing Bacteria on the Corrosion Residual Strength of an AZ91D Magnesium Alloy - Zhu, Xianyong (Materials (Basel), 2014)
In this paper, the corrosion residual strength of the AZ91D magnesium alloy in the presence of sulfate-reducing bacteria is studied. In the experiments, the chemical composition of corrosion film was analyzed by a scanning electron microscope with energy dispersive X-ray spectroscopy. In addition, a series of instruments, such as scanning electronic microscope, pH-meter and an AG-10TA materials test machine, were applied to test and record the morphology of the corrosion product, fracture texture and mechanical properties of the AZ91D magnesium alloy. The experiments show that the sulfate-reducing bacteria (SRB) play an important role in the corrosion process of the AZ91D magnesium alloy. Pitting corrosion was enhanced by sulfate-reducing bacteria. Corrosion pits are important defects that could lead to a significant stress concentration in the tensile process. As a result, sulfate-reducing bacteria influence the corrosion residual strength of the AZ91D magnesium alloy by accelerating pitting corrosion.